2019
DOI: 10.3390/electronics8050517
|View full text |Cite
|
Sign up to set email alerts
|

Laplace Prior-Based Bayesian Compressive Sensing Using K-SVD for Vibration Signal Transmission and Fault Detection

Abstract: Vibration signal transmission plays a fundamental role in equipment prognostics and health management. However, long-term condition monitoring requires signal compression before transmission because of the high sampling frequency. In this paper, an efficient Bayesian compressive sensing algorithm is proposed. The contribution is explicitly decomposed into two components: a multitask scenario and a Laplace prior-based hierarchical model. This combination makes full use of the sparse promotion under Laplace prio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 23 publications
0
4
0
Order By: Relevance
“…The CNN model is originally a two-dimensional (2D) neural network with a 2D matrix as input. With the deepening of the research, it has been found that CNN also has a strong feature extraction ability for onedimensional timing signals and has achieved good results in the vibration signal processing (Ma et al, 2020), fault diagnosis (Khan et al, 2018), natural language recognition (NLP; Zhao et al, 2018;Zhang et al, 2017) and other fields.…”
Section: Principles Of the Convolutional Neural Networkmentioning
confidence: 99%
“…The CNN model is originally a two-dimensional (2D) neural network with a 2D matrix as input. With the deepening of the research, it has been found that CNN also has a strong feature extraction ability for onedimensional timing signals and has achieved good results in the vibration signal processing (Ma et al, 2020), fault diagnosis (Khan et al, 2018), natural language recognition (NLP; Zhao et al, 2018;Zhang et al, 2017) and other fields.…”
Section: Principles Of the Convolutional Neural Networkmentioning
confidence: 99%
“…Generally, an accurate reconstruction algorithm means more running time. Referring [29], the Lap-CBCS-KSVD algorithm can be seen as one of the most accurate algorithms. However, it costs much more time than traditional basic pursuit (BP), orthogonal matching pursuit (OMP) algorithms.…”
Section: Dbn For Cs Compressed Signalmentioning
confidence: 99%
“…Yuan and Chen proposed a fault diagnosis method for rolling bearings based on compression sensing, even under fluctuating working conditions [31]. Ma et al proposed a Bayesian compressed sensing method based on Laplacian priors and utilized K-singular value decomposition (K-SVD) for transmitting vibration signals and detecting faults [32]. Based on the compressed sensing method, efficient reconstruction of low-resolution fault signals of bearings is achieved.…”
Section: Introductionmentioning
confidence: 99%